Post-learning stress reduces the misinformation effect: effects of psychosocial stress on memory updating - Nitschke, Jonas P.; Chu, Sonja; Pruessner, Jens C.; Bartz, Jennifer A.; Sheldon, Signy (Psychoneuroendocrinology, 2019)
•Post-encoding stress reduced likelihood of falsely incorporating, or updating, information.•This effect remained when memory for the events was tested after a multi-day delay.•The impaired flexibility of memory generalisation, that often accompanies stress, can be beneficial by reducing memory intrusions.•Results highlight the dynamic relationship between stress and memory. Episodic memories can be modified when exposed to new and related information. This phenomenon, known as memory updating, is generally thought to be adaptive but can also lead to incorporating false information into a memory trace. Given the well-known effects of stress on episodic memory, we used a false information paradigm to investigate if acute stress during memory updating (i.e., post-learning stage) affected false memory formation. In a between-subject design, young healthy participants completed the initial phases of the misinformation experiment - they studied an event via a slideshow and then were exposed a related narrative that contained misleading information about that event. After, half of the participants were exposed to acute psychosocial stress and the other half completed a control task. Once stress levels returned to baseline, all of the participants completed the final phase of the experiment, which was a memory test for slideshow that included items containing true facts and misinformation. Participants in the stress condition showed a reduced misinformation effect and were better able to discriminate true from false information compared to control participants. This pattern of results held even when participants were tested on the same memory test after a multiple day delay, illustrating the long-lasting effects of stress on false memory formation specifically, and memory updating generally. We discuss how our results add to the understanding of the time-dependent factors that moderate stress effects on memory, and speculate how stress effects on memory updating can be positive, by limiting intrusions into encoded events, but also negative, by limiting the ability to integrate information with other concepts, harming memory generalization.